Regularities of Plasma-Immersion Formation of Long-Pulse High-Intensity Titanium Ion Beams; Russian Physics Journal; Vol. 61, iss. 7 - Ryabchikov A. I. Aleksandr Ilyich; Sivin D. O. Denis Olegovich; Shevelev A. E. Aleksey Eduardovich; Ananin P. S. Petr Semenovich (2018, 2018)
Title screen